Issues of qualification of crimes against life and health - O. Artyushina (Правоприменение)
The subject. The key and, in the author's opinion, the most interesting questions of thequalification of intentional crimes for life and health are determined in a strategic waybased on the study of scientific literature and materials of judicial practice, as well as monitoringof contemporary reality.The purpose of the paper is to investigate the problems of redundancy and the gap in thecriminal law in this area, as well as the difficulties in applying the relevant norms, takinginto account the recommendations of the Plenum of the Supreme Court of the Russian Federation.The methodological basis of the work is dialectical-materialistic, logical, historical, systemstructural,as well as comparative-legal and concrete sociological methods.The main results and scope of it’s application. It is proposed to decriminalize the beatingsprovided for in Art. 116 of the Criminal Code of the Russian Federation, with the introductionof appropriate changes to the version of Article 116.1 of the Criminal Code of the RussianFederation. The problem of an absolute gap in the field of criminal and legal protectionof the individual from new types of causing death and involving minors in a suicidal behaviorpattern, including using the Internet, is being raised. A draft of Federal Law No. 118634-7,submitted by I.A. Yarovaya in March 2017, is overviewed and practical recommendationsfor improving the criminal legislation of Russia are formulated.Conclusions. After the analyzing the most difficult cases of competition, the conclusion isbased on the decisive significance of the expert's conclusion about the presence or absenceof affect for the qualification of these crimes. In order to avoid a superficial approach to lawenforcement and, as a consequence, judicial errors, it is proposed to oblige the courts ineach case, when establishing relevant facts, to appoint a forensic expert examination tocheck whether the perpetrator has a sudden violent emotional excitement (affect).